Houseboat mystery. - Warner, Gertrude Chandler, 1890-1979.; Cunningham, David, 1938- (Chicago, A. Whitman, 1967)
The Alden family rents a houseboat to drift down the river, and encounters a mystery in the little towns along the river, involving a fast black car.
Keywords: Boxcar children (Fictitious characters) -- Juvenile fiction; Orphans -- Juvenile fiction; Families -- Juvenile fiction; Brothers and sisters -- Fiction; Orphans -- Fiction; Mystery fiction